Model Susceptible Infected Removed (SIR) Penyebaran COVID-19 di Indonesia Menggunakan Metode Runge Kutta - Andriyani, Devy; Gunawan, Gani; Suhaedi, Didi (Bandung Conference Series: Mathematics, 2023)
Abstract. COVID-19 first emerged in 2019 in Wuhan, the capital of Hubei Province, China and spread around the world to date. The rapid spread of the virus has made researchers interested in modeling the spread of the virus. Research on epidemiological mathematical models regarding COVID-19, one of which was conducted by Mohamed Lounis & Dilip Kumar Mugal who estimated the parameters of the SIR COVID-19 model in Algeria, in this study will be carried out prediction of the peak of the spread of COVID-19 in Indonesia with mathematical modeling susceptible, infected, removed removed (SIR). Prediction of the peak of the spread is done using the Order 4 Runge Kutta method and python software. From a series of tests that have been carried out, the results of predicting the peak of the spread of COVID-19 in Indonesia occurred around October to November 2020. Based on comparisons with actual data, there was a difference in the results of peak spread where in the prediction can only predict one peak of spread, in fact there are 2 peak spreads, namely November to December 2020 and January 2021 to February 2021. And the spread of the COVID-19 virus will be close to zero at 550 days after March 2020, which is around September 2021. Abstrak. COVID-19 pertama kali muncul pada tahun 2019 di Wuhan, Ibukota Provinsi Hubei, Tiongkok dan menyebar ke seluruh dunia hingga saat ini. Penyebaran virus yang sangat cepat membuat para peneliti tertarik untuk membuat model penyebaran virus tersebut. Penelitian tentang model matematika epidemiologi mengenai COVID-19 salah satunya dilakukan oleh Mohamed Lounis & Dilip Kumar Bagal yang melakukan estimasi parameter model SIR COVID-19 di Aljazair, pada penelitian ini akan dilakukan prediksi puncak penyebaran COVID-19 di Indonesia dengan pemodelan matematika Susceptible, Infected, Removed (SIR). Prediksi puncak penyebaran dilakukan dengan menggunakan metode Runge Kutta Orde 4 dan software python. Dari serangkaian pengujian yang telah dilakukan maka diperoleh hasil prediksi puncak penyebaran COVID-19 di Indonesia terjadi pada sekitar bulan Oktober hingga November 2020. Berdasarkan perbandingan dengan data actual, ditemukan perbedaan hasil puncak penyebaran dimana pada prediksi hanya dapat memprediksi satu kali puncak penyebaran, pada kenyatannya terjadi 2 kali puncak penyebaran yaitu bulan November hingga Desember 2020 serta Januari 2021 hingga Februari 2021. Dan angka penyebaran virus COVID-19 akan mendekati nol pada 550 hari setelah bulan Maret 2020 yaitu sekitar bulan September 2021.